1991
DOI: 10.1002/cber.19911240203
|View full text |Cite
|
Sign up to set email alerts
|

Zum Koordinationsverhalten von Alkinylphosphanen RnP(CC–R')3–n

Abstract: Coordination Ability of Alkynylphosphines RnP(CC – R')3 – n Alkynylphosphines RP(CC–R')2 (2) react with one equivalent of octacarbonyldicobalt to yield selectively the η2‐μ side‐on‐coordinated alkyne complexes (R)(R' – CC)P[(η2‐CC–R')Co2(CO)6] (6); with another equivalent of Co2(CO)8 the dicoordinated compounds (R)P[(η2‐CC–R')Co2(CO)6]2 (7) are obtained. 7 may also be synthesized directly by the reaction of 2 with two equivalents of Co2(CO)8. However, P(CC–Ph)3 yields with two equivalents of Co2(CO)8 the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 25 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…The reaction of RSeC"CPh (1a, R = Et; 1b, R = n-Bu; 1c, R = Ph; 1d, R = 2,4,6-Me 3 C 6 H 2 ) with equimolar amounts of Fe 2 (CO) 9 (2) produces, upon evolution of CO and colour change from yellow to dark red, the diiron hexacarbonyl complexes [(l-SeR)(l-r,p-C"CPh)]Fe 2 -(CO) 6 (3a, R = Et; 3b, R = n-Bu; 3c, R = Ph; 3d, R = 2,4,6-Me 3 C 6 H 2 ) in tetrahydrofuran at 25°C (Eq.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The reaction of RSeC"CPh (1a, R = Et; 1b, R = n-Bu; 1c, R = Ph; 1d, R = 2,4,6-Me 3 C 6 H 2 ) with equimolar amounts of Fe 2 (CO) 9 (2) produces, upon evolution of CO and colour change from yellow to dark red, the diiron hexacarbonyl complexes [(l-SeR)(l-r,p-C"CPh)]Fe 2 -(CO) 6 (3a, R = Et; 3b, R = n-Bu; 3c, R = Ph; 3d, R = 2,4,6-Me 3 C 6 H 2 ) in tetrahydrofuran at 25°C (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Seyferth et al [1,2] reported on the synthesis and reaction chemistry of [(l-SR)(l-r,p-C"CR 0 )]-Fe 2 (CO) 6 (R = R 0 , R 6 ¼ R 0 ; R,R 0 = singly bound organic ligand) (type A molecule) by reacting Fe 2 (CO) 9 with RSC"CR 0 . A further possibility to prepare structural type A molecules is given by the reaction of [Et 3 NH][(l-SR)(l-CO)Fe 2 (CO) 6 ] with allylic or propargylic halides [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations